Recent advancements in durable and self-healing oil well cement: A pathway to secure carbon sequestration - Yan Xie; Michelle Tiong; Qi Liu; Tong Wu; Wanzhen Xue; Chunkai Wang (Journal of CO2 Utilization)
Carbon capture, utilization, and storage (CCUS) technology plays a critical role for significantly reducing greenhouse gas emissions. The integrity of the cement sheath in storage wells is essential to secure the subsurface CO2 storage, however, acidic CO2 can erode the cement sheath over time, leading to chemical and mechanical damages of cement, risking CO2 leakage. The advancement of nanotechnology has introduced nanomaterials into cementing operations, enhancing oil well cement durability against storage conditions due to their high surface area and reactivity. To enhance the security of CO2 storage, it is proposed to incorporate self-healing materials into the cement, which autonomously repair microcracks to maintain the cement sheath's sealing integrity. This review firstly discusses the hydration and carbonation processes of in wellbore cement, and evaluates the influences of various nanomaterials on the cement durability. Subsequently, the self-healing mechanisms of such cement is introduced, along with the effects of different materials on the self-healing performance of oil well cement. Finally, by analyzing existing research achievements and issues, the future important research directions are provided.